The Konsekuensi Penerapan Mix Promosi terhadap Kinerja Pemasaran Bisnis Mikro Kecil dan Menengah di Kabupaten Kampar, Provinsi Riau - Samsurijal Hasan (COSTING : Journal of Economic, Business and Accounting, 2020)
Small and Medium Enterprises is one of the priority programs from Indonesia government is to improve the regional and national economy. Since this industry become the backbone of a populist economic system that is not only intended to reduce the problem of inequality between income groups and between businesses, or alleviating poverty and employment. Unfortunately, Business competition is tight at this time is a challenge for businesses to remain in the global competition. Entrepreneurs who cannot meet consumer tastes will increasingly be left behind and businesses will not develop. Determining the effect of Promotion Mix on the Marketing Performance of Micro, Small and Medium Enterprises in Kampar District is the main objective of this study. The independent variable in this study is the promotion mix and the dependent variable is marketing performance. The analytical model used is a simple linear regression analysis. The number of samples in this study was 96 respondents. The sampling technique uses accidental sampling. Based on the results of the study it can be concluded that there is a significant effect of the promotion mix variable on the Marketing Performance of Micro, Small and Medium Enterprises in Kampar District. Promotional mix variables and marketing performance have a strong relationship with the promotion mix contribution to marketing performance are also quite high at 67.60% determined by promotional mix variables, while the remaining 32.40% is determined by other factors outside the model. It is recommended to MSME entrepreneurs in Kampar Regency, to increase product promotion so that MSME entrepreneurs maintain personal sales because they are most sought after by consumers, so that by increasing personal sales, it will improve the marketing performance of MSME entrepreneurs in Kampar Regency. Keywords: Promotion Mix, Marketing Performance, Small and Medium Micro Enterprise, Kampar